The purpose of this study is to analyze the internal and external environmental factors that influence the marketing strategy at PT Indo Agro Ekosistem. The research is conducted as a case study at PT Indo Agro Ekosistem in Temanggung Regency, Cent - A. N. H. A., Ubaidah; Putri, B. R. T.; Kayana, I G. N. (Jurnal Peternakan Tropika; Vol 12 No 2 (2024): Vol. 12 No. 2 Tahun 2024; March - April, 2024)
The purpose of this study is to analyze the internal and external environmental factors that influence the marketing   strategy at PT    Indo Agro Ekosistem. The research is conducted as a case study at PT   Indo Agro Ekosistem in Temanggung Regency, Central Java Province. The total number of respondents is 33 individuals, comprising 30   respondents   who are consumers of beef in Temanggung Regency, and 3 expert respondents from both internal stakeholders   (Owner,   Manager)   and   external stakeholders (Related Government Department) who possess relevant experience. The data sources utilized include primary and secondary data. Data is collected through observation, in-depth interviews, and interviews assisted by questionnaires. The analysis consists of three stages: 1) an internal and external business analysis to identify strengths, weaknesses, opportunities, and threats, which   will be incorporated   into the   IFE and EFE matrices; 2) the IE matrix is utilized to determine the business's position; 3) SWOT analysis   is   employed   to   formulate   alternative marketing strategies for beef products at PT Indo Agro Ekosistem.